The cowboy's baby blessing - Kastner, Debra (Kastner, Debra. Cowboy country., 2017)
Rachel Perez needs a handyman to spruce up her in-home day care. So when she "wins" ex-soldier Seth Howell in a bachelor auction, she's glad he can swing a hammer. But when freewheeling Seth suddenly inherits a two-year-old and a sprawling ranch, he's got to grow up fast. Seth admires Rachel's kindness and easy way with kids, so he seeks her help in finding his footing as a father. And single mom Rachel sees how determined Seth is to do right by little Caden. Between his toddler and her teenager, they've got plenty of responsibilities. Finding time for love seems out of the questionbut soon they're forging a new familytogether.